2009
DOI: 10.4067/s0717-65382009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Alfred Russel Wallace and the Darwinian Species Concept: His Paper on the Swallowtail Butterflies (Papilionidae) of 1865

Abstract: Soon after his return from the Malay Archipelago, Alfred Russel Wallace published one of his most significant papers. The paper used butterflies of the family Papilionidae as a model system for testing evolutionary hypotheses, and included a revision of the Papilionidae of the region, as well as the description of some 20 new species. Wallace argued that the Papilionidae were the most advanced butterflies, against some of his colleagues such as Bates and Trimen who had claimed that the Nymphalidae were more ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Darwin's botanical contacts Joseph Hooker and Asa Gray also understood and accepted Darwin's views on species (Gray 1888;Endersby 2008). All of these Darwinists simply addressed speciation in different terms than today: their aim was to elucidate any causes of divergence leading to separate species identified via gaps, rather than to attempt to unify species via a single explanation or essence, such as reproductive isolation (Mallet 2008c(Mallet , 2009). Darwin's new view of species in The Origin seemed, at least in the midnineteenth century, crucial to accepting 'transmutationism,' the evolutionary transition between species, as well as the proposed mechanism, natural selection, by which it occurred.…”
Section: Darwin's View Of Speciesmentioning
confidence: 99%
“…Darwin's botanical contacts Joseph Hooker and Asa Gray also understood and accepted Darwin's views on species (Gray 1888;Endersby 2008). All of these Darwinists simply addressed speciation in different terms than today: their aim was to elucidate any causes of divergence leading to separate species identified via gaps, rather than to attempt to unify species via a single explanation or essence, such as reproductive isolation (Mallet 2008c(Mallet , 2009). Darwin's new view of species in The Origin seemed, at least in the midnineteenth century, crucial to accepting 'transmutationism,' the evolutionary transition between species, as well as the proposed mechanism, natural selection, by which it occurred.…”
Section: Darwin's View Of Speciesmentioning
confidence: 99%
“…Not long after Darwin's publication of ‘The Origin of Species’, Wallace (1865) laid out a classification scheme for distinct stages in the formation of species based on observations of swallowtail butterflies. Mallet has recently suggested that this may have been ‘the first attempt by a Darwinist to enumerate and classify the … “varieties” that Darwin argued were the forerunners of species’ (Mallet, 2009: 40). Darwin, Wallace, and their followers thus represented the first wave of interest in understanding the stages of the speciation process.…”
Section: The Birth Of Ecotypementioning
confidence: 99%
“…The crux of Darwin's long argument in the Origin of Species was that natural selection drives the formation of varieties and that these varieties then evolve into species. Although many have argued over Darwin's true beliefs on speciation (Mayr, 1947; Mallet, 2008a, b, 2009; Schemske, 2010), Wallace (1865) articulated the first known classification scheme for stages in the formation of species (Mallet, 2009). The biosystematists, beginning with Turesson (1922a, b) and peaking with the books by Clausen and Dobzhansky in 1951, represent the second wave of interest in ‘stages’.…”
Section: The Third Wave: Contemporary Views On Stages In the Formatiomentioning
confidence: 99%
“…Despite his difficulties in disentangling species boundaries 25 , Wallace 1 used estimates of species richness to hypothesize that the Greater Sunda Islands (especially Borneo) were the ancestral area of this clade from which it later dispersed towards Australia (a similar pattern has also been found in other clades 3 ). Wallace postulated that ‘settling down’ was a strong factor in island speciation (here referred to as founder-event speciation), especially for these good dispersers, and further argued that island features and environmental factors subsequently fostered morphological variation and eventually contributed to speciation (corresponding to the hypothesis of Wallacea acting as a species pump).…”
mentioning
confidence: 99%